“If Only My Foundry Knew What it Knows ...”: A 7Epsilon Perspective on Root Cause Analysis and Corrective Action Plans for ISO9001:2008 - Rajesh Ransing (Proceedings of the 61nd Annual Technical Conference on Investment Casting, Covington, KY, USA, October 5-8, 2014, 2014)
The 7Epsilon penalty matrix approach visualizes factor-response in-process data so that variation in process settings (i.e. measurable factors) that are correlated to variation in response can be identified. The method is applicable to any multivariate data analysis project for root cause reasoning to develop new hypotheses, identify and carry out corrective actions for reduction in variation of response. It can be used to analyze in-process data for investment casting process including all of its sub processes like wax pattern making, shell making, melting, casting, heat treatment etc. The paper describes how an investment casting foundry benefitted by implementing the 7steps of the 7Epsilon methodology for continual process improvement as per the requirements of the clause 8 of the ISO9001:2008 standard. Further opportunities have also been identified for process improvement case studies. Authors have realized that the foundry industry, whether its aerospace or automotive, investment casting or sand casting, needs to address a cultural issue regarding reusing of process knowledge and in-process data in decision making for continual process improvement projects. The role of trade associations as well as a pathway for operator training within 7Epsilon continual process improvement philosophy has been discussed. It is hoped that the panel discussions and the conference environment will provide useful feedback/insights for all stakeholders.